Analysis of tamoxifen and its metabolites in dried blood spot and volumetric absorptive microsampling: comparison and clinical application - Baitha Palanggatan Maggadani; Yahdiana Harahap; Harmita; Samuel J. Haryono; Christoffel William Putra Untu (Heliyon, 2021)
This research was conducted to develop the Dried Blood Spot (DBS) and Volumetric Absorptive Microsampling (VAMS) method in the analysis of Tamoxifen (TAM) and its metabolites endoxifen (END), 4-hydroxytamoxifen (4-HT), and N-desmethyltamoxifen (NDT) using Ultra High Performance Liquid Chromatography-Tandem Mass Spectrometry (UPLC-MS/MS). This method was then applied to monitor TAM and its metabolites in breast cancer patients. The UPLC-MS/MS method was developed and validated with propranolol as the internal standard. The recovery and matrix effects on DBS and VAMS were investigated. The validation requirements were fulfilled by the methodology of analysis and sample preparation described in this study. Both VAMS and DBS extraction recoveries were satisfactory, with low variability. Extraction recovery in the VAMS sample was found to be slightly higher than in the DBS sample. Sample stability in DBS and VAMS was demonstrated for up to 2 months. Both of these methods were successfully applied for the analysis of TAM and metabolites in clinical patients. The mean concentrations obtained from the two methods were not significantly different.